An Amundsen Sea source of decadal temperature changes on the Antarctic continental shelf - Sybren S. Drijfhout; Christopher Y. S. Bull; Helene Hewitt; Paul R. Holland; Adrian Jenkins; Pierre Mathiot; Alberto Naveira Garabato (Ocean Dynamics, 2024)
Mass loss from the Antarctic Ice Sheet is dominated by basal melting–induced warm ocean water. Ice-sheet mass loss and thinning of buttressing ice shelves occur primarily in the Amundsen and Bellingshausen Seas. Here, we show that in a global ocean simulation using the 0.25° Nucleus for European Modeling of Ocean (NEMO) model driven by the JRA55 reanalysis from 1982 to 2017, the Amundsen sector of the Antarctic continental shelf acts as a gateway, regulating the on-shelf access of warm Circumpolar Deep Water (CDW) from the deep ocean and its westward transfer to other sectors up to ca. 90° E, particularly the Ross Sea. As a result, anomalies in Antarctic-shelf-averaged temperature mainly originate in the Amundsen sector. These changes are primarily governed by shifts in the Amundsen Sea Low associated with tropical climate variability, modulating the on-shelf transport of CDW via wind-driven perturbations to ocean currents. The ensuing temperature anomalies progress westward from the Amundsen Sea via three distinct routes: a slow, convoluted westward pathway on the shelf via the Antarctic Coastal Current; a faster westward pathway along the shelf break via the Antarctic Slope Current and then onto the shelf along topographic troughs; and a third, eastward route toward the Bellingshausen sector, whereby temperature anomalies are transported into a region of local wind-generated changes farther north. These results emphasize the importance of the Amundsen sector for climate variability over the Antarctic shelves.

Southern Ocean warming and Antarctic ice shelf melting in conditions plausible by late 23rd century in a high-end scenario - Pierre Mathiot; Nicolas C. Jourdain (Ocean Science, 2023)
How much Antarctic ice shelf basal melt rates can increase in response to global warming remains an open question. Here we describe the response of the Southern Ocean and ice shelf cavities to an abrupt change to high-end atmospheric conditions plausible by the late 23rd century under the SSP5-8.5 scenario. To achieve this objective, we first present and evaluate a new 0.25∘ global configuration of the NEMO (Nucleus for European Modelling of the Ocean NEMO System Team, 2019) ocean and sea ice model. Our present-day simulations demonstrate good agreement with observational data for key variables such as temperature, salinity, and ice shelf melt rates, despite the remaining difficulties to simulate the interannual variability in the Amundsen Sea. The ocean response to the high-end atmospheric perturbation includes a strengthening and extension of the Ross and Weddell gyres and a quasi-disappearance of sea ice, with a subsequent decrease in production of High Salinity Shelf Water and increased intrusion of warmer water onto the continental shelves favoured by changes in baroclinic currents at the shelf break. We propose to classify the perturbed continental shelf as a “warm–fresh shelf”. This induces a substantial increase in ice shelf basal melt rates, particularly in the coldest seas, with a total basal mass loss rising from 1180 to 15 700 Gt yr−1 and an Antarctica averaged melt rate increasing from 0.8 to 10.6 m yr−1. In the perturbed simulation, most ice shelves around Antarctica experience conditions that are currently found in the Amundsen Sea, while the Amundsen Sea warms by 2 ∘C. These idealised projections can be used as a base to calibrate basal melt parameterisations used in long-term ice sheet projections.

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Sensitivity of coastal polynyas and high-salinity shelf water production in the Ross Sea, Antarctica, to the atmospheric forcing - Pierre Mathiot; Nicolas C. Jourdain; Bernard Barnier; Hubert Gallée; Jean Marc Molines; Julien Le Sommer; Thierry Penduff (Ocean Dynamics, 2012)

Influence of coupling on atmosphere, sea ice and ocean regional models in the Ross Sea sector, Antarctica - Nicolas C. Jourdain; Pierre Mathiot; Hubert Gallée; Bernard Barnier (Climate Dynamics, 2011)